Development for E-Module for Plant Physiology Courses to Increase Student’s Critical Thinking Skills - Ayun, Anisa Qurota; Balqis, Balqis; Susilo, Herawati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
This media development aims to develop, validate, practicality and effectiveness of e-modules designed to enhance critical thinking skills in Plant Physiology Course. The e-module focused on plant translocation, cell respiration, and development and growth factors. The research follows R&D using the Lee & Owens model, which includes five stages (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The study involved 33 third-semester biology education students at the State University of Malang. Result from the validation process show that the media achieved a 95% validation rate, categorized as